O29 Pharmacometric modelling of free thyroxine dynamics after initiation of antithyroid drug treatment in children with Graves' disease: a tool for personalized drug dosing in children. Issue 6 (17th May 2019) - Koch, G; Gotta, V; Ollagnier, C; Konrad, D; Flück, C; L'Allemand, D; Steigert, M; Rohner, A; Bachmann, F; Schropp, J; Szinnai, G; Pfister, M
Abstract : Background: Thyroid hormones are essential for normal growth and puberty in children and adolescents. Graves' disease (GD) is a rare autoimmune disorder associated with thyroid hormone over-production and occurs in 0.5–2:100'000 children (mostly females) in Europe. In contrast to adults, first line treatment of GD is long-term antithyroid drug (ATD) therapy, and radioiodine ablation is usually being reserved for patients after puberty. However, treatment of acquired hyperthyroidism with ATD is difficult since 1) paediatric patients differ considerable in age, weight and diseases severity and 2) minimal ATD dose should be used to avoid mild side effects (occurring in 6–35% of patients), and rare severe side effects such as agranulocytosis and liver failure. Methods: Longitudinal clinical and laboratory data from a Swiss multicentre cohort were analysed retrospectively. Non-linear mixed effects modelling was applied to characterize dynamics of free thyroxine (FT4) during the first 3 months of treatment with carbimazole. Sex, co-medications such as propranolol, and thyroid stimulating hormone receptor antibody were tested as covariates on model parameters. Reference range for FT4 was derived from target levels in clinical practice (12–22 pmol/L). Results: Study cohort comprised 45 children with GD, 78% females, median age 12.2 years (IQR = [8.7, 13.6])) with a total of 181 visits. FT4 baseline at diagnosis of GD was 62.3 pmol/L (IQR = [45.7, 86.7]). None of the tested factors showed significant covariate effects. The model allows individual simulations of optimal ATD dosing strategies (starting and maintenance dose) for different GD severities, ages and weights at start of therapy. Personalized dosing examples will be presented. Conclusions: Developed pharmacometric model is able to predict dynamics of FT4 in children with GD depending on four parameters: ATD dose/kg/d, age, weight and disease severity, and can be applied to personalize dosing regimen to avoid over- or under dosing. Disclosure(s): Nothing to disclose